2020
DOI: 10.1038/s41467-020-18365-0
|View full text |Cite
|
Sign up to set email alerts
|

Efficient rational modification of non-ribosomal peptides by adenylation domain substitution

Abstract: Non-ribosomal peptide synthetase (NRPS) enzymes form modular assembly-lines, wherein each module governs the incorporation of a specific monomer into a short peptide product. Modules are comprised of one or more key domains, including adenylation (A) domains, which recognise and activate the monomer substrate; condensation (C) domains, which catalyse amide bond formation; and thiolation (T) domains, which shuttle reaction intermediates between catalytic domains. This arrangement offers prospects for rational p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
93
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(103 citation statements)
references
References 72 publications
8
93
0
2
Order By: Relevance
“…The suitable recombination sites between the Cs and A domains need to be further investigated in detail for the efficient engineering of lipopeptides. The recently reported research on the modification of NRPSs by A domain alone substitution also supported that C domain specificities were not as strict as we previously thought 36 . Our results suggested that the use of full-length Cs domain as a swapping unit is a feasible way to modify lipopeptides.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The suitable recombination sites between the Cs and A domains need to be further investigated in detail for the efficient engineering of lipopeptides. The recently reported research on the modification of NRPSs by A domain alone substitution also supported that C domain specificities were not as strict as we previously thought 36 . Our results suggested that the use of full-length Cs domain as a swapping unit is a feasible way to modify lipopeptides.…”
Section: Discussionsupporting
confidence: 83%
“…Thus, the reason for the failure could be donor specificity of the downstream C domain. The relatively broad specificities of RzmA-Cs and HolA-Cs to acceptor substrates explain why the aforementioned Cs domain swapping led to the successful production of acyl-changed rhizomide, holrhizin, and glidobactin derivatives, and support the very recent study that novel nonribosomal peptides can be generated by the substitution of A domains alone 36 . Subdomain (N-lobe) swapping of GlbF-Cs with that of GlpC-Cs was also conducted, but no expected compounds were detected.…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…Therefore, selection of recombination events that maintain the structural integrity of the C–A interface appears plausible, although recent engineering studies have proofed that the C–A linker can be exploited for the reengineering of domains ( Bozhüyük et al. 2018 ; Calcott et al. 2020 ; Kaniusaite et al.…”
Section: Discussionmentioning
confidence: 99%
“…Given the antibiotic resistance crisis, a detailed understanding of their underlying biosynthetic mechanisms becomes increasingly important to help in facilitating the exploitation of NRPS templates by combinatorial approaches for the discovery of new compounds. [1][2][3][4][5] The structural and functional organization of NRPSs is reminiscent of an assembly line. Arrays of single domains act together in a sequential manner to synthesize the peptide product from N to C terminus under the consumption of ATP.…”
Section: Introductionmentioning
confidence: 99%